Kobieta jako pokusa dla mnicha według Ewagriusza z Pontu - Misiarczyk, Leszek (Vox Patrum, 2016)
The article presents the teaching of Evagrius of Pontus on women. The author stresses the need to embed evagrian reflection in the context of strict monastic life and asceticism without which a monk of Pontus appears as mizoginist. Evagrius in his texts on women teaches anchorites three things. Firstly, it reminds them that they have chosen the life in the desert and should avoid any encounters with women. They have to stay rather in their cells praying instead of participating the local feasts and games. Secondly, it encourages that during the meetings on the occasion of spiritual direction monks should be extremely prudent and that this task is more proper to the senior monks. Thirdly, it teaches how to cleanse the soul and mind from the images of women.